MENGEMBANGKAN BUDAYA SEKOLAH YANG MENDUKUNG ANTI- PERUNDUNGAN MELALUI KEBIJAKAN DAN NILAI-NILAI - Purba, Benedict J (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
This article discusses how schools can develop a culture that supports bullying prevention through clear policies and the implementation of positive values. The main goal of this article is to highlight the importance of firm and sustainable policies in addressing bullying, as well as how values such as empathy, mutual respect, and tolerance can create a safe and inclusive atmosphere within schools. The approach used includes a literature review on theories of bullying prevention, as well as an analysis of existing policies in Indonesia, such as the Child Protection Law and education regulations. Findings from this article reveal that effective anti-bullying policies not only impose sanctions on perpetrators of bullying but also focus on prevention through proactive education and character building. Additionally, reinforcing positive values, such as respecting differences, fostering solidarity, and developing social skills, is crucial in creating an inclusive school culture that supports student development. This article also suggests that schools should not rely solely on reactive policies but should adopt a more holistic approach by involving all stakeholders, including teachers, students, parents, and the community, to create a safe, comfortable, and supportive learning environment for all students.